PENGARUH CELEBRITY ENDORSEMENT DAN TESTIMONI TERHADAP MINAT BELI PENGGUNA MEDIA SOSIAL INSTAGRAM PADA DAVIENA SKINCARE SANGATTA - Rahmatia Basyah, Thaarika; Amransyah, Amransyah; Irma, Irma (Sekolah Tinggi Ilmu Ekonomi Nusantara Sangatta, 2024)
This study aims to examine the effect of celebrity endorsement and testimonials perception on purchasing interest in buying user social media Instagram at Daviena Skincare Sangatta. In this research, the observed population consists of consumers at Daviena Skincare Sangatta, with a sample of 97 respondents selected to determine the influence of celebrity endorsement, testimonials and interest in buying. Method:The method used in this study is a quantitative approach. Statistical analysis was conducted using SPSS version 21, applying multiple regression analysis to derive. Results: The findings indicate that both celebrity endorsement and testimonial have a positive and significant effect on interest in buying at Daviena Skincare Sangatta